Penerapan Spiritualitas di Tempat Kerja Di RSI F dan Hubungannya dengan Kepuasan Kerja Perawat - Mulyono, Wastu Adi (Jurusan Keperawatan FIKES UNSOED, 2011)
Background.Job satisfaction is significant predictor toward organizational commitment which area one of factors influencing nurse job turnover in hospital with religion background which adopted spiritual values. A research should conduct to investigate relationship between spirituality and job satisfaction. Objective. This research was aimed to identified correlation between spiritual applications and job satisfaction. Method. A case study on RSI F conducted to 84 nurses. Chi square analyses was applied to test the relationship. Results. It was reported that facilitation focused on organization and leadership showed significant relationship p(0,000 and 0,039 on Î±=0,05), however facilitation focused on individual and group showed no significant relationship with job satisfaction p(0,534 and 0,096 on Î±=0,05). Conclusion. Job satisfaction can be improved by facilitating organization spirituality as well as leader spirituality. Recomendation. RSI F was recommended to clarify parameter of vision and mission attainment, and to address spiritual leadership training for manager. Following researches were recommended to broaden area on all hospitals with religion background.